Community empowerment through penta helix collaboration in infrastructure-impacted areas - Annisa Farra Biyyu Dzaky; Nisa Safrina Maulida; Yuli Eka Wulansari; Aryan Yoga Ramadhan; Ekhtya Dharma Cahyono (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: The development of Dhoho International Airport in Kediri Regency represents a strategic government effort to stimulate regional economic growth. Initiated by the private sector through PT SDHI, a subsidiary of PT Gudang Garam, the project has faced challenges from local communities regarding housing and livelihoods. Beyond social shifts, the airport’s operation is expected to trigger broader transformations in education, culture, and economics, necessitating rapid community adaptation. This study aims to analyze the post-development impact on local residents. Methods: This research employs a descriptive qualitative approach grounded in Penta Helix theory, utilizing purposive and snowball sampling for data collection. Findings: The study identifies distinct roles for Penta Helix actors—government as regulators, academics as knowledge providers, private sectors as job creators, media as educators, and civil society as mediators. Strategic planning revealed that community empowerment must integrate local traditions with modern vocational training to optimize economic opportunities. Conclusion: Effective empowerment requires synchronized collaboration where the government acts as the primary controller and policymaker to ensure sustainable welfare. Novelty/Originality of this article: This research provides a localized strategic framework for community empowerment in airport-affected areas, specifically using the Penta Helix model integrated with SWOT-based survey validation.